Hybrid OFDM-Digital Filter Multiple Access PONs Utilizing Spectrally Overlapped Digital Orthogonal Filtering - Abdulai Sankoh; Wei Jin; Zhuqiang Zhong; Jiaxiang He; Yanhua Hong; Roger Philip Giddings; Iestyn Pierce; Maurice O'Sullivan; Jeffrey Lee; Tim Durrant; Jianming Tang (IEEE Photonics Journal, 2020)
Known hybrid orthogonal frequency division multiplexing-digital filter multiple access (OFDM-DFMA) PONs show promise of seamless and cost-effective convergence of optical and mobile networks for 5G and beyond. This paper reports, for the first time, a new hybrid OFDM-DFMA PON based on intensity modulation and direct detection (IMDD), obtained by modifying digital signal processing (DSP) algorithms embedded in both the OLT and ONUs. The proposed PON allows two spectrally overlapped sub-bands to occupy each individual sub-wavelength spectral region to independently transmit upstream ONU information. A model of the proposed PON is developed and its upstream transmission performances are numerically explored for different application scenarios. Compared with the previously published PON, the proposed PON doubles the number of supported ONUs and provides >1.7-fold aggregate upstream signal transmission capacity increases with <1.5 dB upstream power budget degradations. Alternately, for the same ONU count, >2.2-fold aggregate upstream signal transmission capacity increases and >0.7 dB upstream power budget improvements are achievable. The performance improvements vary by <18% for a transmission distance range as large as 50 km. In addition, the proposed PON is tolerant to finite digital filter tap length-induced channel interferences.